Structural concrete finite-element analysis for limit-state design - Kotsovos, M. D. (Thomas Telford, 1995)
Shows the unifying generality of the proposed approach and the reliability of the ensuing computer package, for which the sole input is the specified cylinder strength of concrete and the yield is the stress of steel. This book offers an understanding of structural concrete behaviour, and illustrates the revision required for improving methods.